Inter-regional Wage Dispersion in Portugal - José António Cabral Vieira; Jo\~ao Pedro Almeida Couto; Maria Teresa Borges Tiago (European Regional Science Association (ERSA), 2005)
This paper examines the size o inter-regional wage dispersion in Portugal. For this purpose, we estimate a Mincer-type human capital wage equation, including controls for a large number of districts, and calculate a weighted and adjusted standard deviation (WASD) of inter-regional wage differences. The value is high and quite stable over time. The highest wages are found in the region of Lisbon and the Tagus Valley. We Moreover, is quite sensitive to inclusion of human capital and industry controls.
Keywords: 330